DEVELOPMENT INEQUALITY OF DISTRICT/ CITY IN SOUTH SUMATRA ( 2008 - 2015) - Rohima, Siti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
This study aims to determine the effect of PAD, DAU, regional expenditure andeconomic growth to the development gaps in the province of South Sumatra.The data used is secondary data in the GRDP, regional expenditure, PAD andDAU per district / city in the period 2008- 2015. In this study, using a quantitative approach. Technical analysis of using Williamson index calculation and linear regression. These results indicate that the PAD and Expenditure have a positive effect, on the contrary DAU and economic growth have a significant negative effect on the development gaps District / City in theprovince of South Sumatra. JEL Classification: H70, H77, O10 Keywords: DAU, Development inquality, Economic Growth, PAD, RegionalExpenditure